Tunable Monopole Circular Microstrip Antenna for tuning WLAN, Radar and Satellite Communication Applications - Rajendra, Biradar; Mulgi, SN (International Journal of Computer Sciences and Engineering, 2020)
This paper presents a design and development of slot and stub loaded tunable monopole circular microstrip antenna for different frequency of microwave communication applications. The antenna proposed is loaded with a U-slot, two I-slots and J- slot over the patch. The dimensions of U-slot, J-slot and upper I-slot are fixed. The one of the I-slot loaded over the patch on opposite side of J–slot is varied to achieve tuning in the WLAN, C and X band frequency ranges. When dimensions of I-slot is changed to 0.722cm, 0.755cm and 0.76 cm and corresponding resonant frequencies are lies at 5.815GHz, 4.825GHz and 4.69GHz at left band where as for right band the resonant frequencies are lies at 7.84GHz, 7.7725GHz and 7.8625GHz respectively. The bandwidth required for WLAN band of 5-22MHz is fulfilled in designed antenna and also for C and X bands. The optimum impedance bandwidth (IBW) of proposed antennas for left and right band is 29.43 % and 42.89 % having peak gain of 2.11 dBi and 2.72 dBi respectively. The radiation patterns are omni directional in nature in both E and H plane.